Analysis of a foundational biomedical curriculum: exploring cumulative knowledge-building in the rehabilitative health professions - De Bie, Gabrielle (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2017)
This study was motivated by the researcher's experience that students in the rehabilitative health professional programmes were finding it difficult to access fundamental knowledge upon which their professional practices and clinical contexts are based. An important focus of the research was the extent to which cumulative knowledge-building was impacted after the foundational biomedical curriculum became an interdisciplinary programme. The study explored whether the organisation of the interdisciplinary foundational curriculum served the fundamental needs of the professions, and whether, as a matter of social justice, students' access to powerful knowledge was enabled by the form that the fundamental curriculum assumed. This curriculum study at a particular Faculty of Health Sciences foregrounds the structuring, organisation and differentiation of disciplinary knowledge, and reflects a twenty year period that included not only transitions in professional education but also extensive transformation in, and a different approach to, health delivery. At the institution, physiology and anatomy, the biomedical sciences basic to the health professions, underwent disciplinary merging and subsequent altered positioning in curricula. Medicine opted for a problem-based learning approach whereas the rehabilitation health sciences did not. Legitimation Code Theory (LCT) provided the means for analysis of the extent to which interdisciplinary organisation in the foundational curriculum for Physiotherapy and Occupational Therapy enabled integrative, cumulative building of knowledge for professional and clinical contexts. Specialisation and Semantics dimensions of Legitimation Code Theory were used to reveal the principles underpinning practices, contexts and dispositions of Anatomy and Physiology at the Faculty of Health Sciences over a twenty year period post democratisation in South Africa (1994 - 2013). Disciplinary positioning in curriculum prior- and post-merger, were compared and contrasted. LCT were used to characterise the distinctiveness of Physiotherapy and Occupational Therapy at the university including the kind of knowledge and the kind of knower that specialises the different professions, and what is valorised and legitimated for each kind of professional. Semantic gravity was used to explore the expected knowledge recontextualisations in diverse and complex clinical settings for each of the professions. Registered professionals who are clinical educators as well as curriculum designers for clinical studies were interviewed. Profession-specific course outlines were further data sources. The biomedical disciplines Anatomy and Physiology were characterised for their measures of distinction and their respective knowledge-knower structures. Analysis traced each discipline from its strongly classified form in autonomous curricula when there were separate learner-cohorts for physiotherapists and occupational therapists, to post-merger when the disciplines were framed as human biology in an integrated foundational curriculum for a joint cohort of students. Curricular documents for the twenty year period were analysed quantitatively and qualitatively to establish the positioning of Physiology and Anatomy before and after the disciplines merged to a single course of Human Biology. Teaching staff were interviewed for their understanding of what specialises the physiological and anatomical components of the Human Biology curriculum, what they considered as powerful knowledge for the professions, and who they envisaged as the ideal student-knower exiting the basic sciences platform to enter more advanced clinical studies. The degree of context-dependence for meaning-making in the different disciplinary domains and the condensation of meanings inherent in the respective practices and contexts, were analysed. The thesis argues that following the merger Anatomy is preferentially legitimated as powerful knowledge at the expense of Physiology; that the ideal of disciplinary integration is not reached, and that the segmental organisation and structuring of the curriculum negatively impacted on cumulative knowledge-building and application of professional knowledge in the clinical arena. After the merger the disciplines lost their shape, and in particular the hierarchical knowledge structure of Physiology collapsed. By not having access to the necessary disciplinary knowledge structures and their associated practices, students' ability for scaffolding and integrating knowledge into the clinical arena was constrained. The organisation of the current Human Biology curriculum does not facilitate cumulative learning, and in so doing may not contribute to the envisaged graduate professional who is required to practice within a complex and demanding healthcare work environment. The significance of this study conveys that interdisciplinary programmes should be carefully considered, and there is an added imperative in the health professions which ultimately realise treatment of patients. If, aside from interdisciplinary teaching, there are also merged cohorts of participant students, then a sound understanding of the epistemic requirements of each profession is required. Those involved in curriculum development in various fields need to take these recommendations into account to enable cumulative learning and enable epistemological access to powerful knowledge for an increasingly diverse student body.
Keywords: Medical education -- Curricula; Human anatomy -- Study and teaching -- Curricula; Physiology -- Study and teaching -- Curricula; Occupational therapy -- Study and teaching -- Curricula; Physical therapy -- Study and teaching -- Curricula; Medical rehabilitation -- Study and teaching -- Curricula; Knowledge, Theory of